Development of genomic SSR markers for fingerprinting lettuce (Lactuca sativa L.) cultivars and mapping genes - Rauscher Gilda (BMC Plant Biology, 2013)
Abstract Background Lettuce (Lactuca sativa L.) is the major crop from the group of leafy vegetables. Several types of molecular markers were developed that are effectively used in lettuce breeding and genetic studies. However only a very limited number of microsattelite-based markers are publicly available. We have employed the method of enriched microsatellite libraries to develop 97 genomic SSR markers. Results Testing of newly developed markers on a set of 36 Lactuca accession (33 L. sativa, and one of each L. serriola L., L. saligna L., and L. virosa L.) revealed that both the genetic heterozygosity (UHe = 0.56) and the number of loci per SSR (Na = 5.50) are significantly higher for genomic SSR markers than for previously developed EST-based SSR markers (UHe = 0.32, Na = 3.56). Fifty-four genomic SSR markers were placed on the molecular linkage map of lettuce. Distribution of markers in the genome appeared to be random, with the exception of possible cluster on linkage group 6. Any combination of 32 genomic SSRs was able to distinguish genotypes of all 36 accessions. Fourteen of newly developed SSR markers originate from fragments with high sequence similarity to resistance gene candidates (RGCs) and RGC pseudogenes. Analysis of molecular variance (AMOVA) of L. sativa accessions showed that approximately 3% of genetic diversity was within accessions, 79% among accessions, and 18% among horticultural types. Conclusions The newly developed genomic SSR markers were added to the pool of previously developed EST-SSRs markers. These two types of SSR-based markers provide useful tools for lettuce cultivar fingerprinting, development of integrated molecular linkage maps, and mapping of genes.